Effect of different approaches to target force on transcranial magnetic stimulation responses. Issue 3 (15th July 2013) - Gruet, Mathieu; Temesi, John; Rupp, Thomas; Millet, Guillaume Y.; Verges, Samuel
ABSTRACT Introduction: The aim of this study was to determine whether the manner in which a target force is approached can influence the electromyographic (EMG) and mechanical parameters evoked by transcranial magnetic stimulation (TMS) during brief muscle contractions. Methods: The amplitude of motor‐evoked potentials (MEP) and superimposed twitch and the duration of the silent period were recorded in 8 healthy participants in response to TMS delivered during brief isometric voluntary contractions of the quadriceps maintaining a target force (10% and 50% of maximal voluntary force) or gradually increasing or decreasing to reach this point. Results: MEP and superimposed twitch, unlike the silent period, are influenced by the manner of reaching a low force. Conclusions: Clear instructions must be provided to research participants and patients. Rapidly increasing to a target force without exceeding it and maintaining the force before the delivery of TMS results in stable, representative MEP amplitudes. Muscle Nerve48: 430–432, 2013